Challanges and Changes in the Movie Industry in the Post-COVID Era - Čurma, Ivan (2024)
This paper revolves around the impact of the COVID-19 pandemic on the film industry. COVID-19 affected many industries and reshaped the order of the world in many ways, but few industries were impacted to such extent as the entertainment, and more specifically, the movie industry. The main goal of this thesis is to analyze the impact of the pandemic itself, as well as various other elements that emerged during these years. Furthermore, this paper delves deeper into matters such as the rise of streaming services, generative AI in the movie industry, and the Hollywood strikes that once again halted the entire industry. Among the key sources for this paper, you can find relevant and renowned journals (such as The Washington Post, CNN Business, Forbes, or The Guardian); numerical data collected from various global data and business intelligence platforms (Statista, The Numbers, regional databases like Data USA), as well as utilizing other internet-available sources and books listed at the end of the paper. Though the pandemic and the strikes have already come to a conclusion and the preliminary results can be found in this paper, it will take years to fully understand the impact these last few years had on the industry as a whole.